PENGARUH KEGUNAAN PERSEPSIAN, KEMUDAHAN PENGGUNAAN PERSEPSIAN, NORMA SUBYEKTIF DAN RISIKO PERSEPSIAN TERHADAP PENGGUNAAN AKTUAL APLIKASI PAPERLESS OFFICE DI UNIVERSITAS GADJAH MADA - , Wijayanti, SIP, Dr. Didi Achjari, M.Com. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Rapid information technology development bring major changes in the form of office communication. Electronic communication emerged as a complement to face-to-face communication which later proved to have a positive impact in improving organizational performance. Eventhough the benefits of using electronic communications proven, many people are still reluctant to use it. This study focuses on the application of paperless office as one form of electronic communication. The purpose of the research was to test whether the perception about electronic communication media influence the actual use of paperless office applications among the employee of Universitas Gadjah Mada. Variables used in this study are perceived usefulness and perceived ease of use which are variables of the Technology Acceptance Model (TAM), subjective norm, and perceived risk. Research model was tested with a field survey of 160 paperless office user at Universitas Gadjah Mada using a structural equation model with the program SmartPLS Version 2.0. From the seven hypotheses proposed, six proved significant and one not proved significant. Subjective norms and perceived ease of use found postively significant affect the actual use and the perceived risk proved negatively significant affect the actual use. In general, it can be concluded that the subjective norms have a very important role as the base of application usage, as shown by the positively significant relationship to actual use, either directly or by mediation of perceived usefulness and perceived ease of use.